Mobile Music Store M-Muze - Shuib, Farah Nurshazreen (Universiti Teknologi Petronas, 2006)
The introduction of the mobile devices into the electronic commerce arena has allowed the user to go on the Web as well as shopping on the Web using their cell phones, Personals Digital Assistants (PDAs) or combo devices without needing a wired Internet connection and stationary desktop or a laptop computer. In order to give customer's convenience, service providers and also value-added services include easy, timely access to information in a way enable customer to make purchase from whenever they are whenever they are ready. The author here will develop an instant music CD purchasing via mobile phone application by using Wireless Markup Language (WML) as a programming tool. The technique that has been adopted is based on Wireless Application Protocol (WAP) as global standards for mobile solutions. The result of the study has proven that in order to captivate users' attention towards legal music CD purchasing through the web via mobile, design of the interface has given an impact towards the adaptation of content presentation by implementing HCI elements. Therefore, the design of the interface and content according to one's preference plays an important role in enhancing users' "browse and buy" experience at any desired time and needs. The study done towards the implementation of design guidelines for wireless application which is in general, interface design flaws are platform independent has also proven that the design best applied depends on the form factors of the wireless mobile phones. The system URL: http://www.ideashoppe.com IV